Formation of the model of school management in changing external conditions - V. N. Volkov (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2015)
The article presents the general characteristic of changes in the Russian system of basic education, defines the scientific study of designing of models of school management, capable of ensuring sustainable development in the medium and long term. The author provides the analysis of models of management of educational institutions used in schools and developed in science. Based on the analysis the author formulates general requirements for the model of school management to ensure the effectiveness of its work in the changing external conditions.